Common approaches to introduced species management face widespread acceptance problems in the United States - Wade Simmons; Darragh Hare; Andrea Dávalos; Bernd Blossey (People and Nature)
Abstract Decisions on whether and how to manage introduced species can be controversial, but public attitudes towards introduced species management (ISM) are poorly understood. Despite the potential disruptive impacts of such controversies on public relations and conservation goals, decision‐makers are currently left with little information on the social acceptability of different management alternatives. To better understand the social acceptability of core features of ISM in the United States, we conducted an online experiment with vignettes describing hypothetical but realistic ISM scenarios, varying targeted taxon (insect or plant), control method (mechanical, chemical and biological), risk severity (low and high) and type of non‐target risk (to humans or native species). Not surprisingly, management with low risk was most acceptable, particularly for mechanical control. In high‐risk scenarios, only mechanical control was acceptable, but only by a slim majority of respondents. Overall, chemical and biological controls showed low levels of acceptability. Surprisingly, there was no significant difference in how respondents ranked risks to people and risks to native species. Beyond differences in acceptability between management factors, we also find that the acceptability of management and attitudes towards risk were associated with respondents' demographic characteristics. Policy Implications. Overall, our findings indicate that widespread acceptability of ISM should not be assumed. While management activities representing low‐risk scenarios find some support in the public, our results highlight a disconnect between the effectiveness of common management methods and their social acceptability. Our findings highlight the need for evidence‐guided ISM, which includes evidence of harmful impacts of introduced species, as well as risks and benefits of management activities, as one potential way to increase the social acceptability of non‐native species management. Read the free Plain Language Summary for this article on the Journal blog.